Injectable Nonmagnetic Liquid Metal for Eddy‐Thermal Ablation of Tumors under Alternating Magnetic Field. Issue 9 (18th June 2020) - Yang, Nailin; Li, Wei; Gong, Fei; Cheng, Liang; Dong, Ziliang; Bai, Shang; Xiao, Zhisheng; Ni, Caifang; Liu, Zhuang
Abstract: Hyperthermia induced by the alternating magnetic field (AMF) to heat magnetic nanomaterials localized within the tumor has attracted wide attention due to its ability in effective tumor ablation, low side effects, and deep tissue penetration. However, rather strong AMFs are often needed to realize effective magnetic hyperthermia of tumors. Herein, it is discovered that nonmagnetic gallium–indium liquid metal (GaIn LM) above certain sizes prepared by the shearing force could be effectively heated up under AMF with a low field intensity owing to the eddy‐thermal effect, which could be utilized for AMF‐induced hyperthermia treatment of tumors. As demonstrated in experiments using mice bearing subcutaneous 4T1 breast tumors and rats with deeply seated orthotopic liver tumors, local injection of GaIn LM followed by AMF treatment could result in effective ablation of those tumors. With great in vitro biocompatibility, such GaIn LM also shows no appreciable in vivo toxicity to mice within two months. This work thus presents a new type of thermal ablation therapy using nonmagnetic, biocompatible, and injectable LM to ablate tumors under a low‐field‐intensity AMF, with the eddy‐thermal heating mechanism distinctive from that in conventional magnetic hyperthermia therapies using magnetic nanoagents. Abstract : This work presents a new type of thermal ablation therapy using non‐magnetic, biocompatible, and injectable liquid metal (LM) to ablate tumors under a low‐field‐intensity alternating magnetic field (AMF), with the eddy‐thermal heating mechanism distinctive from that in conventional magnetic hyperthermia therapies using magnetic nanoagents. This biocompatible and injectable GaIn LM would be a promising magnetocaloric agent to destruct deeply seated tumors under a low‐field‐intensity AMF.